Electrochemical Synthesis of Silver Hollow Microsphere Arrays - Han, Chengliang; Tian, Changan; Deng, Chonghai; Ming, Ding (Asian Journal of Chemistry, 2012)
Silver hollow microsphere arrays were fabricated by electrophoresis deposition (EPD) approach based on monolayer polystyrene (PS) colloidal crystal template technique. Every silver hollow microsphere is made of many silver nanoplates which are standing on the surface of microsphere and cross-linking each other. The formation of nanoplates is attributed to oriented-attachment- growth of small silver nanoparticles. This prepared method is reproducibility, inexpensive and easy to make.